Standardisation of in vitro techniques for the rapid clonal propagation of bael (Aegle marmelos (L) corr) - Hazeena M S (Department of Plantation Crops and Spices, College of Agriculture, 2001)
Studies were conducted for evolving in vitro techniques for the rapid clonal propagation of bael [ Aegle marmelos CL.) Corr.] during 1999 - 2001 at Plant Molecular Biology and Biotechnology Centre, College of Agriculture, Vellayani. Attempts were made to standardise in vitro propagation techniques of bael via enhanced release of axillary buds using shoot nodal segments and cotyledons as explants. Entire cotyledons were used as explants for direct organogenesis while cotyledons excluding embryoaxes were used for indirect organogenesis. Among the explants used for enhanced release of axillary buds, cotyledons responded better than nodal segments. Cent per cent survival could be obtained in cultures with cotyledons while a maximum of 50.00 per cent was obtained in cultures with nodal segments. Maximum shoot proliferation from nodal segments was obtained on full strength MS basal medium supplemented with BA 2.50 mgl ", IAA 1.00 mgl ", sucrose 30.00 gr' and agar 8.00 gl'. The best treatment identified for shoot proliferation from cotyledons was full strength MS basal medium supplemented with BA 0.50 gl ", GA3 3.00 mgl', adenine sulphate 20.00 mgl", sucrose 50.00 gl' and agar 5.00 gr'. Maximum initiation of direct organogenesis from cotyledons ( 83.33 per cent ) occurred in two treatments namely, on full strength MS basal